RESEARCH ON SUSTAINABLE DEVELOPMENT OF CHINA’S DIRECT INVESTMENT IN COUNTRIES ALONG THE BELT AND ROAD INITIATIV (ІННОВАЦІЙНА ЕКОНОМІКА, 2025)
Ye Jianfu. RESEARCH ON SUSTAINABLE DEVELOPMENT OF CHINA’S DIRECT INVESTMENT IN COUNTRIES ALONG THE BELT AND ROAD INITIATIVPurpose. This research examines China’s direct investments in Belt and Road Initiative countries, analysing their volumes, directions, sectors, and geographic distribution, while assessing their economic, social, and environmental impacts on partner nations, identifying challenges, and proposing solutions to enhance sustainable development.Methodology of research. The following methods were employed during the research process: Collect, analyse, and compare literature analysis methods suitable for constructing a theoretical framework for China’s investment in the Belt and Road Initiative, and formulate effective suggestions for the challenges and opportunities in the sustainable development process of the Belt and Road Initiative,Formulate relevant policy recommendations and cooperation mechanisms; visual methods.Findings. Established that China’s direct investment along the Belt and Road Initiative encounters significant challenges across multiple domains. Substantiated that political, economic, and legal risks pose major concerns for investment sustainability. Proven that current risk management systems and early warning mechanisms require substantial strengthening. Analysed the critical need for optimizing policy support frameworks. Verified that cooperation mechanisms need enhancement to foster stability. Demonstrated that creating a transparent and predictable investment environment remains essential for long-term success.Originality. This study establishes that effective coordination between government, businesses, and society is essential for sustainable development of China’s Belt and Road investments. Unlike existing frameworks, this approach enables more integrated policy implementation. The research demonstrates that government plays a fundamental role in providing policy support and promoting cooperation. It confirms that enterprises must enhance their risk management and social responsibility mechanisms. Furthermore, it advances our understanding of society’s critical function in building trust and fostering communication between participating nations, which leads to more stable investment environments.Practical value. The research findings have direct practical applications across multiple domains. Government policymakers can use these insights to develop more effective investment policies and risk management frameworks. Financial institutions can enhance their assessment models for Belt and Road projects. Companies planning investments in Belt and Road countries can better evaluate risks and opportunities. Local governments in recipient countries can leverage this research to optimize their investment facilitation policies – maximizing the benefits of Chinese enterprises’ investments while ensuring environmental and social sustainability.Key words: Belt and Road countries, investment facilitation level, foreign direct investment, investment openness, cooperation mechanisms, challenges and countermeasures. Є Цзяньфу. ДОСЛІДЖЕННЯ СТІЙКОГО РОЗВИТКУ ПРЯМИХ ІНВЕСТИЦІЙ КИТАЮ В КРАЇНАХ ІНІЦІАТИВИ «ОДИН ПОЯС, ОДИН ШЛЯХ»Мета. Розгляд прямих інвестицій Китаю в країни, залучені до Ініціативи «Один пояс, один шлях», аналізуються їхні обсяги, напрями, сектори та географічний розподіл, а також оцінюється їхній економічний, соціальний та екологічний вплив на країни-партнери, виявлено проблеми та запропоновано рішення для посилення сталого розвитку.Методологія дослідження. У процесі дослідження використано низку наукових методів, зокрема: збір, аналіз і порівняння літературних джерел, що дозволяють сформувати теоретичну базу для вивчення китайських інвестицій у рамках ініціативи «Один пояс, один шлях»; формулювання ефективних рішень щодо викликів і можливостей сталого розвитку; розробка політичних рекомендацій і механізмів співпраці; а також застосування візуальних методів аналізу.Результати дослідження. Дослідження засвідчило, що прямі інвестиції Китаю в рамках Ініціативи «Один пояс, один шлях» зіштовхуються зі значними труднощами в політичній, економічній та правовій сферах. Доведено, що саме ці ризики є ключовими перешкодами для забезпечення стійкості інвестицій. Встановлено необхідність суттєвого вдосконалення систем управління ризиками та механізмів раннього попередження. Також проаналізовано актуальність удосконалення механізмів політичної підтримки та співпраці, що сприятиме загальній стабільності. Наголошено на важливості створення прозорого та передбачуваного інвестиційного середовища як чинника довгострокового успіху.Наукова новизна результатів дослідження. Дослідження підкреслює важливість ефективної координації між урядом, бізнесом і громадянським суспільством для забезпечення сталого розвитку інвестицій у рамках ініціативи. Запропонований підхід відрізняється від існуючих моделей більш інтегрованим впровадженням політики. Підтверджено ключову роль уряду у формуванні політичної підтримки та стимулюванні міжнародної співпраці. Водночас доведено, що компанії повинні вдосконалити механізми управління ризиками та підвищити рівень соціальної відповідальності. Дослідження також поглиблює розуміння ролі суспільства у формуванні довіри та розвитку міждержавного діалогу, що сприяє стабілізації інвестиційного клімату.Практична значущість результатів дослідження. Результати дослідження мають прикладне значення для широкого кола зацікавлених сторін. Державні органи можуть використовувати їх для розробки ефективнішої інвестиційної політики та удосконалення систем управління ризиками. Фінансові установи можуть застосовувати отримані висновки для поліпшення оцінки проєктів у межах ініціативи. Компанії, які планують інвестувати в країни-учасниці, отримують можливість точніше оцінювати ризики й перспективи. Місцева влада в країнах-реципієнтах може використовувати результати дослідження для оптимізації політики сприяння інвестиціям, забезпечуючи при цьому екологічну та соціальну сталість.Ключові слова: країни «Один пояс, один шлях», рівень сприяння інвестиціям, прямі іноземні інвестиції, інвестиційна відкритість, механізми співпраці, виклики та заходи.